English Students Perception Toward E-Learning during COVID-19 in University Level at Surabaya - Hertiki Hertiki; Shafinah Md. Salleh; Robby Maulana Abrori Rosdiansah (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
In COVID-19 pandemic, many activities cannot be carried out as normal, especially in the field of education. Therefore, the government has determined that offline learning is temporarily suspended and learning is carried out online. However, E-learning has many conveniences, there are also obstacles that give rise to various student perceptions. The purpose of this study was to describe student perceptions of E-learning during the COVID-19 period at the university level in Surabaya. This research method uses descriptive qualitative research. The informants in this study were 17 English students in the year 2020 from classes A, B, and E, at PGRI Adi Buana University, Surabaya. Data collection techniques used in this study were questionnaires and interviews. The analytical technique used is the descriptive analysis technique. The results of the study revealed that most of the students had negative perceptions at first. This is due to constraints in infrastructure and connectivity such as poor internet, limited internet data and lack of suitable devices. Students have difficulty understanding the material because unstable connections affect their understanding of the material. In addition, not all lecturers have a good strategy for teaching using E-Learning, and some students feel bored. One of the students also felt stressed with homework. In addition, they have difficulty communicating with their friends and lecturers. Overall, students consider E-learning effective during the pandemic because it is able to overcome obstacles such as connectivity problems, operate LMS (Zoom Meeting, Google Meet, Virlenda) and also all applications (Kahoot, WordWall).